Transanal rectal resection: an initial experience of 20 cases. (January 2016) - Buchs, N. C.; Nicholson, G. A.; Yeung, T.; Mortensen, N. J.; Cunningham, C.; Jones, O. M.; Guy, R.; Hompes, R.
Abstract: Aim: Low anterior resection (LAR) can present a formidable surgical challenge, particularly for tumours located in the distal third of the rectum. Transanal total mesorectal excision (taTME) aims to overcome some of these difficulties. We report our initial experience with this technique. Method: From June 2013 to September 2014, 20 selected patients underwent transanal rectal resection for various malignant and benign low rectal pathologies. All patients with rectal cancer were discussed at a multidisciplinary team meeting. Data were entered into a prospective managed international database. Results: Of the 20 patients (14 male), seventeen (85%) had rectal cancer lying at a median distance of 2 cm (range 0–7) from the anorectal junction. The operations performed included LAR (16). Abdominoperineal excision (2) and completion proctectomy (2), all of which were performed by a minimally invasive approach with three conversions. The mean operation time was 315.3 min. There were six postoperative complications of which two (10%) were Clavien–Dindo Grade IIIb (pelvic haematoma and a late contained anastomotic leakage). The median length of stay was 7 days. The TME specimen was intact in 94.1% of cancer cases. The mean number of harvested lymph nodes was 23.2. There was only one positive circumferential resection margin (tumour deposit; R1 rate 5.9%). One patient developed a distant recurrence (median follow‐up 10 months, range 6–21). Conclusion: TaTME was safe in this small series of patients. It is especially attractive in patients with a narrow and irradiated pelvis and a tumour in the lower third of the rectum. TaTME is technically demanding, but the good outcomes should prompt randomized studies and prospective registration of all taTME cases in an international registry.